Effect of saline conditions on chemical profile and the bioactive properties of three red-colored basil cultivars - Cruz, Luís Royer Oliveira (2018)
The present study investigated the effect of salinity (Control: 1.8 dS/m, S1: 3.0 dS/m and S2: 4.5 dS/m) on the chemical composition and bioactive properties of three basil cultivars (Red Basil, Dark Opal Red and Basilico Rosso). Crop performance was not affected by increasing salinity in DoR and BaR. Fat, ash and carbohydrates content increased by salinity in DoR, whereas energetic value was negatively affected. Free sugars (total and individual compounds) increased under saline conditions (S2) in BaR, whereas reducing trends were observed for the main organic acids and tocopherols in all the cultivars. The major fatty acids were α-linolenic, linoleic and palmitic acids with no consistent salinity effects, while the richest polyphenols were sagerinic acid and eriodictyol-O-malonylhexoside. Finally, basil extracts showed moderate antioxidant and strong antifungal activity. In conclusion, salinity showed a genotype dependent effect on the chemical profile and bioactivities of the tested cultivars.